2017
DOI: 10.1093/cid/cix1032
|View full text |Cite
|
Sign up to set email alerts
|

Rigorous Clinical Trial Design in Public Health Emergencies Is Essential

Abstract: Randomized clinical trials are the most reliable approaches to evaluating the effects of new treatments and vaccines. During the 2014-2015 West African Ebola epidemic, many argued that such trials were neither ethical nor feasible in an environment of limited health infrastructure and severe disease with a high fatality rate. Consensus among the numerous organizations providing help to the affected areas was never achieved, resulting in fragmented collaboration, delayed study initiation, and ultimately failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…A cross-cutting theme identified was the need to strengthen collaboration and coordination between organisations involved in outbreak response at all levels [3,7,81]. Effective partnerships between countries and international organisations, such as public health, clinical research organisations, non-governmental organisations (NGOs), pharmaceutical companies and regulatory agencies, were described as instrumental for success [3,14,16,19]. International research collaborations should be tied to capacity building and be genuinely collaborative [22], with local stakeholders engaged from inception [1, 3, 13, 16-19, 22, 26, 29, 31, 32, 36, 38, 40, 44, 50, 51].…”
Section: Strengthen Collaboration and Coordinationmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-cutting theme identified was the need to strengthen collaboration and coordination between organisations involved in outbreak response at all levels [3,7,81]. Effective partnerships between countries and international organisations, such as public health, clinical research organisations, non-governmental organisations (NGOs), pharmaceutical companies and regulatory agencies, were described as instrumental for success [3,14,16,19]. International research collaborations should be tied to capacity building and be genuinely collaborative [22], with local stakeholders engaged from inception [1, 3, 13, 16-19, 22, 26, 29, 31, 32, 36, 38, 40, 44, 50, 51].…”
Section: Strengthen Collaboration and Coordinationmentioning
confidence: 99%
“…Shaw et al [73] Ethical and social solutions identified (Table 4) The temporal and spatial variation in the risk of infection during outbreaks presents not only statistical hurdles but also an ethical challenge for study designs [75]. Previous research responses have highlighted the many challenges in agreeing on simultaneously ethical, scientifically valid and acceptable study designs [18,36,42,51,59,64,66], addressing socially valuable questions [14,18,64,66]. The exclusion of children and pregnant women was an ethical concern during the Ebola outbreak in LMICs [18,69], compounded by challenges of obtaining complex consent [2, 4, 5, 15, 18, 21, 25, 32, 34, 44-46, 50, 69, 70].…”
Section: Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In the context of public health emergencies, conducting a randomized clinical trial can be even more challenging. 4 The shortfalls of the contemporary clinical trial system include the increasingly prohibitive costs, local and national regulatory requirements, delays in approval, and unnecessary trial processes. 5 Over the past decade, innovations in trial design have been deployed to facilitate trial conduct.…”
mentioning
confidence: 99%
“…Experienced colleagues demonstrated that RCT, even in such difficult circumstances, was not only feasible but the only reliable way that could provide proper guidance, in contrast to the empirical strategies employed during pandemic times. 26 Many different trials evaluating anticoagulants and other strategies for both VTE prophylaxis and treatment are currently ongoing. Reliable data will be available soon, but until then, physicians should do what has been proven to be efficient and safe and in case of uncertainty randomize patients into ongoing clinical trials.…”
Section: Final Considerationsmentioning
confidence: 99%